Association between neutrophil to lymphocyte ratio and erectile dysfunction among US males: a population-based cross-sectional study - Feng, Xingliang; Mei, Yangyang; Wang, Xiaogang; Cui, Li; Xu, Renfang (Frontiers in Endocrinology, 2023)
Objective The purpose of the study was to investigate the relationship between neutrophil-to-lymphocyte ratio (NLR) and erectile dysfunction (ED) in adult American males using a large database. Methods We adopted a series of statistical analyses of the relationship between NLR indices and ED prevalence among participants in the 2001-2004 National Health and Nutrition Examination Survey (NHANES) database using the R software. Results The study included a total of 3012 participants, of whom 570 (18.9%) presented with ED. NLR levels were 2.13 (95% CI: 2.08,2.17) in those without ED and 2.36 (95% CI: 2.27,2.45) in those with ED. After adjusting for confounding variables, NLR levels were higher in patients with ED, (β, 1.21, 95% CI, 1.09-1.34, P < 0.001). In addition, a U-shaped relationship between NLR and ED was observed after controlling for all confounders. A more significant correlation (β, 1.35, 95% CI, 1.19 to 1.53, P < 0.001) existed to the right of the inflection point (1.52). Conclusion The results of the large cross-sectional study showed a statistically significant association between the occurrence of ED and NLR, a simple, inexpensive, and readily available parameter of inflammation, in US adults. Further studies are still needed in the future to validate and replicate our findings and to investigate the specific mechanisms involved.